Study of Mass and Facade Change in Muara Baru Modern Fish Market, North Jakarta - Ika Safitrah; Nur Kharismawati Utami (Department of Architecture, Faculty of Engineering and Computer Science, Universitas Muhammadiyah Semarang, 2025)
This study is about the composition of mass and facade at the Muara Baru Modern Fish Market in North Jakarta, focusing on the application of modern architecture. This study aims to identify the composition of mass and facade at the Muara Baru Modern Fish Market building in North Jakarta by knowing the influence and development between the old and new buildings. The research method used is descriptive qualitative, with data collection through observation, documentation, and literature analysis. The results of the study show that the form of the Muara Baru Modern Fish Market mass composition adopts a functional and aesthetic design, with facade elements inspired by fish scales, creating a strong visual identity. The use of modern materials such as glass and metal gives a dynamic and fresh impression, supporting the theme of the sea and fisheries. This study is expected to provide new insights in the application of metaphorical architecture to commercial buildings, as well as being a reference for the development of modern fish market designs in Indonesia. Thus, the Muara Baru Modern Fish Market not only functions as a trading centre but also as an example of modern architectural innovation that can change people's views of traditional markets to be more attractive and environmentally friendly.